The Effectiveness Of Gallery Walk Method In English Language Learning For Health Science Students - Nandita Wana Putri Nandita; Apri Damai Sagita Krissandi (Alinea: Jurnal Bahasa, Sastra dan Pengajaran, 2026)
The gallery walk method is an active learning strategy based on group rotation that encourages interaction and discussion among students. This study aims to analyze students' perceptions of the effectiveness of the gallery walk method in English language learning for health science students in Bandar Lampung. The study employed a quantitative descriptive approach using a questionnaire distributed to 85 students from Panca Bhakti School of Health Sciences (n=58) and Baitul Hikmah School of Health Sciences (n=27). The instrument consisted of 28 items covering five dimensions: (1) engagement and learning motivation, (2) improvement in English proficiency, (3) relevance to health needs, (4) implementation and execution of learning, and (5) collaboration and interaction among groups. The measurement scale used a 1–5 Likert scale. The results showed an overall mean of 4.42 (SD=0.60), indicating a very positive perception. The highest dimension was engagement and motivation (M=4.47), followed by English proficiency improvement and implementation (M=4.43), and medical relevance and collaboration (M=4.39). The most highly rated items were that the Gallery Walk makes learning more interesting (M=4.59) and creates a livelier classroom atmosphere (M=4.57). The lowest scores were for grammar mastery and vocabulary retention (M=4.32), reflecting the method’s communicative rather than form-focused orientation. In conclusion, the Gallery Walk is perceived as highly effective in enhancing motivation, engagement, and the contextual relevance of English learning in health education settings. These findings are based on student self-reports and do not constitute experimental evidence of proficiency gains.